Lebensschutz aus frei-evangelischer Sicht: ein theologisch-ethischer Beitrag aus freikirchlicher Perspektive - Iff, Markus (Catholica <Münster>, 2024)
This article develops and explains a free-church perspective on life protection at the beginning of life as a contribution to the current debate on the abolition of Section 218 of the German Criminal Code on abortion, it presents and discusses a biblical-theological and life-world oriented context for the justification of ethical judgement. This is linked to guiding principles of theological anthropology and guidelines for ethical behaviour on the tense relationship between self-determination and life protection. This also involves the question of whether prenatal life is a protected good of the legal community or whether its protection should be left to the attitudes, convictions, and interests of social individuals. The narrow focus of the discussion on abortion on reproductive self-determination is viewed critically.